Research Trends on the Effect of Good Corporate Governance (GCG) on Company Profitability - Judijanto, Loso; Qosim, Nanang (West Science Accounting and Finance, 2024)
This study employs a bibliometric analysis to explore the relationship between Good Corporate Governance (GCG) and company profitability, analyzing the evolving themes within corporate governance research from 2000 to 2024. By mapping the density of keywords and assessing co-authorship networks, the research identifies core themes that persistently resonate within the literature: corporate performance, risk management, and the integration of sustainability practices. The analysis reveals a strong correlation between effective governance structures and enhanced corporate profitability, emphasizing the role of governance in risk mitigation and strategic decision-making. Additionally, the study highlights a significant shift in focus towards sustainability and corporate social responsibility, aligning with global trends towards ethical business practices. The findings suggest that adaptive governance practices are vital for sustaining profitability and ethical integrity in the face of evolving global business challenges and regulatory landscapes. This study contributes to the understanding of how GCG influences company profitability and informs future research directions in the field of corporate governance.